Highlights of the 2nd international symposium on tribbles and diseases: tribbles tremble in therapeutics for immunity, metabolism, fundamental cell biology and cancer - Cui, Bing (2019)
The Tribbles (TRIB) family of pseudokinase proteins has been shown to play key roles in cell cycle, metabolic diseases, chronic inflammatory disease, and cancer development. A better understanding of the mechanisms of TRIB pseudokinases could provide new insights for disease development and help promote TRIB proteins as novel therapeutic targets for drug discovery. At the 2nd International Symposium on Tribbles and Diseases held on May 7-9, 2018 in Beijing, China, a group of leading Tribbles scientists reported their findings and ongoing studies about the effects of the different TRIB proteins in the areas of immunity, metabolism, fundamental cell biology and cancer. Here, we summarize important and insightful overviews from 4 keynote lectures, 13 plenary lectures and 8 short talks that took place during this meeting. These findings may offer new insights for the understanding of the roles of TRIB pseudokinases in the development of various diseases. (C) 2019 Chinese Pharmaceutical Association and Institute of Materia Medica, Chinese Academy of Medical Sciences.